2012
DOI: 10.1111/j.1399-5618.2012.00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory acuity is associated with mood and function in a pilot study of stable bipolar disorder patients

Abstract: Objectives Olfactory dysfunction is described in several neuropsychiatric disorders but there is little research on olfactory processing in bipolar disorder. Methods We assessed odor detection threshold (sensitivity) and smell identification test scores along with symptoms, cognition, and social function in 20 DSM-IV bipolar disorder patients and 44 control subjects. Results The patient and control groups had similar demographic measures, intelligence, and mean olfaction scores, but significantly differed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 57 publications
9
48
3
Order By: Relevance
“…Although our findings were not robust to correction for multiple comparisons, we found an indication that olfactory performance may be associated with illness severity and global functioning in individuals with bipolar disorder and depression. Similar relationships between olfactory performance and clinical symptom severity were previously reported in bipolar disorder and depression . In schizophrenia, olfactory dysfunction persists at every phase of the illness, with deficits observed in the prodromal period and worsening over the disease course .…”
Section: Discussionsupporting
confidence: 78%
“…Although our findings were not robust to correction for multiple comparisons, we found an indication that olfactory performance may be associated with illness severity and global functioning in individuals with bipolar disorder and depression. Similar relationships between olfactory performance and clinical symptom severity were previously reported in bipolar disorder and depression . In schizophrenia, olfactory dysfunction persists at every phase of the illness, with deficits observed in the prodromal period and worsening over the disease course .…”
Section: Discussionsupporting
confidence: 78%
“…Olfactory dysfunction appears to be a promising vulnerability marker of schizophrenia (e.g., Turetsky et al, 2009b), and early studies have reported relatively intact olfactory function in BD (Burón and Bulbena, 2013). However, several recent studies have demonstrated olfactory impairment in BD and a relationship to their affective (Cumming et al, 2011;Hardy et al, 2012) or psychotic (Striebel et al, 1999) symptomatology as well as social functioning (Hardy et al, 2012;Lahera et al, in press), which could be partly attributable to a close functional and neuroanatomical relationship between olfactory ability, emotional processing, and social cognition (Soudry et al, 2011;Lahera et al, in press). The present MRI results of abnormally shallow olfactory sulcus in BD partly support these olfactory ability findings, as this anatomical abnormality could be associated with embryonic disruption of olfactory system development (Abolmaali et al, 2002;Hummel et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies suggest a close relationship between olfactory and affective information processing, with common underlying neural substrates including limbic structures (Soudry et al, 2011). Although olfactory function in bipolar disorder (BD) has not been well documented (Burón and Bulbena, 2013), several recent studies have demonstrated olfactory dysfunction in BD (Cumming et al, 2011;Hardy et al, 2012;Lahera et al, in press) or in a BD subgroup with psychotic symptoms (Striebel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Results include, but are not limited to, circadian rhythms (e.g., aryl hydrocarbon receptor nuclear translocator‐like BmaL1 (ARNTL) and RAR‐related orphan receptor B (RORB), neuronal development (e.g., neurotrophic factors and DISC1) , calcium metabolism (e.g., CACNA1C and RASGRP1) , monoamine metabolism (e.g., TPH1 A218C) , mitochondrial function (e.g., POLGI) and cell survival . Notwithstanding, effect sizes for most susceptibility genes are low, results are often inconsistent, and discriminant power is insufficient for clinical utility .…”
Section: Resultsmentioning
confidence: 99%